Exploring the adaptability and applicability of military mental skills training for South African paramedics - Minnie, Chantel (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
Paramedics in South Africa are among the best in the world (MacFarlane, van Loggerenberg, & Kloeck, 2005). However, the domain of pre-hospital emergency care is fraught with challenges and paramedics face numerous personal and professional difficulties. South Africa, with its diverse patient population and challenges, cannot afford to undermine the importance of supportive interventions for emergency medical technicians. Whilst there is a growing body of literature examining the effectiveness of mental skills training in the sporting domain (Gould, Dieffenbach, & Moffett, 2002; Landers & Boutcher, 1998), there is a lack of research on mental skills training as it pertains to paramedics. It is argued here, that the use of mental skills training derived from sporting science and adapted for the military, provides the most comparable context in relation to the paramedic industry. This study thus aims to explore the adaptability and applicability of military mental skills training techniques in the context of South African paramedics. This study made use of an exploratory, qualitative case study design, focusing on participatory research strategies. The analysis revealed that various aspects of existing military mental skills models can be adapted to be of relevance in the emergency medical services field as it related to three paramedic participants. A prominent emerging theme was that of PTSD among paramedics, and it was an area that the participants felt should receive much more attention, research and intervention.
Keywords: Allied health personnel -- South Africa; Allied health personnel -- Mental health -- South Africa; Post-traumatic stress disorder -- South Africa; Emergency medical services -- Psychological aspects